Entomotherapy and its potential applications in Panama - Atencio V, Randy (2023)
Objective. To analyze the application of entomotherapy and its potentialin Panama. Methods. The study is a brief analysis of the application ofentomotherapy worldwide and the establishment of a list of 20 potentialarthropod species that could be used for this purpose in Panama, compiling a total of 26 scientifc articles from digital databases associated with the subject. Results. Entomotherapy encompasses the study of the medicinal use of insects and other arthropods in continents such as Africa, America, Asia, Europe andOceania. Although there are ample references to the use of insects and other arthropods for medical treatments within the traditions of various human groups, in Panama the information associated with this subject is very limited, despitebeing a diverse country both in culture and in species of arthropods, mainly insects. Conclusions. Twenty examples of arthropods used in entomotherapy in different regions of the world and some in Panama are presented, with potential to be used in pharmacological studies for the treatment of certain pathologiesin the country.